Inter-Species Redox Coupling by Flavin Reductases and FMN-Dependent Two-Component Monooxygenases Undertaking Nucleophilic Baeyer–Villiger Biooxygenations - Andrew Willetts (Microorganisms, 2022)
Using highly purified enzyme preparations throughout, initial kinetic studies demonstrated that the isoenzymic 2,5- and 3,6-diketocamphane mono-oxygenases from Pseudomonas putida ATCC 17453 and the LuxAB luciferase from Vibrio fischeri ATCC 7744 exhibit commonality in being FMN-dependent two-component monooxygenases that promote redox coupling by the transfer of flavin reductase-generated FMNH2 by rapid free diffusion. Subsequent studies confirmed the comprehensive inter-species compatibility of both native and non-native flavin reductases with each of the tested monooxygenases. For all three monooxygenases, non-native flavin reductases from Escherichia coli ATCC 11105 and Aminobacter aminovorans ATCC 29600 were confirmed to be more efficient donators of FMNH2 than the corresponding tested native flavin reductases. Some potential practical implications of these outcomes are considered for optimising FMNH2-dependent biooxygenations of recognised practical and commercial value.